Supply chain disturbances and resilience strategies: a secondary data study - Carvalho, Helena (2019)
This research is funded by Fundação para a Ciência e Tecnologia (project MIT-Pt/EDAM-IASC/0033/2008 and project PTDC/EME-GIN/68400/2006). The principal author was supported by a PhD fellowship from Fundação para a Ciência e Tecnologia (SFRH/BD/43984/2008).